2011
DOI: 10.1093/ejechocard/jer263
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic right ventricle longitudinal contraction indices cannot predict ejection fraction in post-operative Fallot children

Abstract: Three conventional echocardiographic indices based on RV longitudinal contraction failed to assess the EF in our population of post-operative tetralogy of Fallot patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 30 publications
3
24
0
1
Order By: Relevance
“…However, a smaller study of TOF in an age group comparable with ours also found that TAPSE failed to predict RVEF on CMR. 11 In agreement with this smaller study, our data suggest that TAPSE is not discriminative, sensitive, or specific for identifying patients with TOF with reduced RVEFs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, a smaller study of TOF in an age group comparable with ours also found that TAPSE failed to predict RVEF on CMR. 11 In agreement with this smaller study, our data suggest that TAPSE is not discriminative, sensitive, or specific for identifying patients with TOF with reduced RVEFs.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are in contrast to those of some studies but in agreement with the results of others. 11,12,27 Van der Zwaan et al 27 studied patients with heart failure and affected right and/or left ventricles and found a modest correlation of TAPSE with RVEF on CMR (correlation coefficient = 0.4). In TOF, Koestenberger et al 12 found a modest correlation (correlation coefficient = 0.47) between TAPSE and RVEF measured on CMR.…”
Section: Discussionmentioning
confidence: 99%
“…As well, the RV can be especially difficult to image reliably in this population because of its dilation and retrosternal location. 26,27 CMR is not hindered by these drawbacks, typically provides high-quality and reproducible imaging data sets, and has become the modality of choice in the assessment of ventricular size and function in many forms of adult congenital heart disease, including TOF. 28,29 For these reasons, we used a CMR-based approach in this study.…”
Section: Discussionmentioning
confidence: 99%
“…24,28 The trabeculations were included in the RV area measurements to avoid underestimating the areas. 9,12,29 The RV endocardial areas were delineated for three consecutive cardiac cycles and the mean of the three values were used to compute FAC. 29 The RV FAC was automatically calculated from the EchoPAC™ software analysis as follows: 100 x [RV end-diastolic area (cm 2 ) – RV end-systolic area (cm 2 )]/ RV end-diastolic area (cm 2 ), (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…24,28 Care was taken to include the trabeculations in the measurements of the area by tracing the RVEDA and RVESA between RV trabeculations and the compact layer of the ventricle. 9,12,29 The RVESA and RVEDA were measured at the frames just before tricuspid valve opening and just after the valve closure, respectively. 5,10 Fractional area of change = 100 x ((RVEDA (cm 2 ) - RVESA (cm 2 )) / RVEDA (cm 2 ).…”
Section: Figurementioning
confidence: 99%